Hybrid transanal and laparoscopic hand-assisted TME for low rectal cancer: report of a case - Samalavičius, Narimantas Evaldas; Dulskas, Audrius; Aliukonis, Vygintas; Račkauskas, Rokas; Kilius, Alfredas (Lietuvos chirurgija, 2016)
Total mesorectal excision (TME) is a widely accepted golden rectal cancer surgery standard. In low rectal cancer, there are a lot of important concerns related to sphincter saving, positive resection margins and similar aspects. We present a case of 52 year old female, who underwent a successful hybrid transanal and laparoscopic hand-assisted TME for low rectal cancer. Trials to delineate proper indications for low rectal cancer of robotic TME, transanal TME (Ta TME) and hybrid transanal plus laparoscopic TME are needed.
Keywords: total mesorectal excision; transanal dissection; rectal cancer